Abstract method of upper and lower solutions and application to singular boundary value problems: Dedicated to Professor Ioan A. Rus on the occasion of his 80th anniversary - PRECUM, Radu (Studia Universitatis Babeș-Bolyai Mathematica, 2016)
The method of upper and lower solutions is presented for the fixed point problem associated to operators which are compositions of a linear operator and a nonlinear mapping. Spectral properties of the linear part together with growth and monotonicity properties of the nonlinear part are involved. An application to singular boundary value problems is included. Mathematics Subject Classification (2010): 47J25, 47H07, 34B16, 34B18.